Low-latitude mesospheric mean winds observed by Gadanki mesosphere-stratosphere-troposphere (MST) radar and comparison with rocket, High Resolution Doppler Imager (HRDI), and MF radar measurements and HWM93 - Kumar, G. Kishore; Ratnam, M. Venkat; Patra, A.K.; Rao, V.V.M. Jagannadha; Rao, S. Vijaya Bhaskar; Kumar, K. Kishore; Gurubaran, S.; Ramkumar, G.; Rao, D. Narayana (My University, 2008)
[1] Low-latitude mesospheric winds are investigated using data collected from 1995 to 2006 (11 years) by Indian MST radar located at Gadanki (13.5°N, 79.2°E). Clear eastward and westward flow in zonal wind is noticed during solstices and equinoxes, respectively. The meridional wind shows equatorward flow below 75 km and poleward flow above 75 km quite consistent with that observed with other techniques. The winds show a clear semiannual oscillation (SAO) with maxima during equinoxes. The strength of the SAO during spring is larger than that of fall equinox, and the first peak occurs at higher altitudes than the second peak. The observed features are compared with other techniques, namely, rocket, High Resolution Doppler Imager (HRDI), and medium frequency (MF) radar and also with horizontal wind model HWM93. In general, good comparison is seen among various techniques, with some discrepancy observed in amplitudes. Interestingly, decrease in eastward wind with time during winter months is noticed. The significance of the present results lies in showing the consistency/inconsistency of various experimental techniques to measure the middle atmospheric winds, which are very important to assess the climate variability.
Keywords: Mesospheric winds; MF radar; MST radar; Rocket; Climatology; HRDI; HWM93